Theories of counseling and psychotherapy : a multicultural perspective - Ivey, Allen E.; D'Andrea, Michael (Michael John); Ivey, Mary Bradford (Thousand Oaks : SAGE Publications, 2011)
'This book is a core text for the counseling theories course which is offered in departments of psychology, counseling, and mental health, in general. It is a required, foundational course, which lays the groundwork for the rest of the curriculum in most mental health programs. The Ivey book is known for having the deepest integration of a multicultural framework among all other theories books. The book covers all the basic theories of counseling such as psychodynamic, Alderian, Jungian, Cognitive-Behavioral, Rational Emotive Behavior therapy, Existential and Humanistic, Logotherapy and Gestalt counseling'--Provided by publisher.
13. Positive Psychology/Wellness Counseling and Brief/Solution-Focused Therapy Chapter Goals Vignette #13 An Integral Approach to Counseling and Psychotherapy Introduction The Wellness Counseling Model Implementing a Personal/Contextual Approach to Wellness Counseling Brief/Solution-Focused Therapy and Wellness Counseling Limitations and Practical Implications of Brief/Solution-Focused Therapy and Positive Psychology/Wellness Counseling Summary Professional Development Extension 14. Developmental Counseling and Therapy- Integrative Theory and Practice Chapter Goals Vignette #14 An Integral Approach to Counseling and Psychotherapy Introduction The Integrative Worldview of Developmental Counseling and Therapy DCT's Approach to Treatment Planning The Unique Narrative Strategies of DCT Limitations and Practical Implications of the DCT Integrative Approach Summary Professional Development Extension 15. Family Counseling and Therapy: Theoretical Foundations and Issues of Practice Chapter Goals Vignette #15 An Integral Approach to Counseling and Psychotherapy Introduction Origins of a Family Perspective The Systemic Worldview Central Constructs of Family Counseling and Therapy Major Family Counseling and Psychotherapy Theories Classifying Systemic Therapies Limitations and Practical Implications of Family Counseling and Therapy Summary 16. Identifying Your Own Integrated Approach to Counseling and Therapy Chapter Goals An Integral Approach to Counseling and Psychotherapy Introduction The Search for the'Best' Theory A Summary of the Four Major Theoretical Forces of Counseling and Psychotherapy Constructing Your Own View or Theory of Counseling and Therapy References Name Index Subject Index.
Book is accompanied by two computer laser optical discs entitled' Theories of counseling and psychotherapy : a multicultural perspective' bearing the same call number and available at Koleksi Media (level 2, PTSL).
Includes bibliographical references : (pages 689-716) and indexes.
Keywords: Psychotherapy -- methods; Counseling -- Methods; Cultural Diversity